Neonatal Home Care Practices and Care Seeking Behaviour in Rural Makwanpur of Nepal - Baral, Kedar Prasad; Hunter, K.L.; Poudel, Sudarshan; Koirala, S.; Rezai, T.; Upadhyay, Shambhu Kumar (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study assesses the state of newborn home-care practices and care-seeking behaviors among the recently delivered mothers to better inform the behavior change communication efforts for effective implementation of the program. Methods: A descriptive study was conducted in two village development committees of Makwanpur district from June to July 2011. A total of 214 women, residing for six months or more in study areas and delivered within past one year, were interviewed using questionnaires designed to collect quantitative and qualitative data. Results: Eighty eight percent of the respondents practiced exclusive breastfeeding, 44% dried and wrapped their newborn within the first five minutes following delivery and 84% used a clean instrument to cut the umbilicus. Ninety-five percent of mother accessed antenatal care from a skilled health provider, 77% of mothers completed four antenatal care visits and only 13% of mothers accessed postnatal care. The first place the mothers would go for seeking care for the neonates was the Primary Health Care Center (54%) followed by the traditional practitioners (20%) and private clinics (6%). The low quality of services at Primary Health Care Center was the most commonly cited barrier to care-seeking (22%) followed by staff unavailability, behaviour and poor counselling. Conclusions: Effective implementation of community-based integrated newborn care program will require engaging stakeholders in both short-term behaviour change communication strategies and long-term commitments to improving quality of care.